Urban heritage streets revitalisation: identification of attributes and development of ranking and strategy / Zalina Samadi - Samadi, Zalina (2015)
This study focuses on the revitalisation performance of the outdoor ambience in between heritage streets. The heritage streets in this study is limited to an abundance of shop houses within the core zone o f the historic city of the Straits of Malacca; George Town in Pulau Pinang and Melaka. The existing physical and spiritual attributes of the ‘outdoor space in between the heritage street is currently in various conditions that requires urgent monitoring system of revitalisation. The spaces have a high potential to be enhanced as ‘an urban outdoor living room' with magnetic attraction as “a place” for promoting onstreet cultural heritage products and environment. The vibrancy o f pedestrian movement of the observed study area has the regenerative potentials to create a positive aura with unique, antique and authentic ambience. Thus, the outdoor space quality reflects a high economic, environmental and social value. With this awareness, the study aims to unfold the “constructive approach” of the ambience with three main objectives. The first objective is to identify the heritage street Revitalisation Attribute (RA) and develop the Revitalisation Toolkit (RT). RA is the “construct” and RT is the “measuring tool” of the heritage street revitalisation performance (RP). The second objective is to investigate the experts' decision-making using Expert Choice for Revitalisation Ranking (RR) of heritage streets. The highest rank street leads to the third objective which is to develop the Revitalising Strategy (RS). In terms of methodology, this study employs mixed methods o f unobtrusive and obtrusive research. The unobtrusive research employs document analysis and Direct Visual Assessment (DVA) and the obtrusive research employs Focus Interview (FI) with experts in Melaka and George Town, Pulau Pinang. The findings of this research are the identification of RA, and the development of RR and RS. The research findings provide an integrated monitoring system for the identification of RA and development of toolkit for ranking and strategy towards valorising the urban outdoor quality o f the heritage streets.